2001
DOI: 10.1007/s004420100744
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of different ant species as partners of a myrmecophilous butterfly

Abstract: We assessed the quality of different ant species as partners of the facultatively myrmecophilous lycaenid butterfly Glaucopsyche lygdamus. We compared disappearance and parasitism rates of G. lygdamus larvae in the field, and development of non-feeding prepupae in the laboratory, when individuals were untended or tended by one of four ant species. Formica podzolica was the only ant species to provide a clear benefit to G. lygdamus, in the form of reduced larval parasitism relative to untended larvae. F. 'neoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 37 publications
1
41
0
1
Order By: Relevance
“…Both parasitoids are lycaenid specialists known to attack the larvae of a wide range of genera (Arnaud, 1978;Marsh, 1979; reported by Fraser et al, 2001). Cotesia cyaniridis attacks the lycaenid Glaucopsyche lygdamus feeding on Lupinus sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both parasitoids are lycaenid specialists known to attack the larvae of a wide range of genera (Arnaud, 1978;Marsh, 1979; reported by Fraser et al, 2001). Cotesia cyaniridis attacks the lycaenid Glaucopsyche lygdamus feeding on Lupinus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Cotesia cyaniridis attacks the lycaenid Glaucopsyche lygdamus feeding on Lupinus sp. in Colorado (Pierce & Mead, 1981;Fraser et al, 2001), and another species of Cotesia is known to attack the lycaenid Polyommatus coridon feeding on Hippocrepis comosa in southern France (Schurian et al, 1993). Likewise, the tachinid A. theclarum has been reported to attack other species of lycaenid (Pierce & Mead, 1981;Fraser et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this observation the parasitoid did not land on the larva, but later on, when collected at the end of its 4 th instar, it had been parasitized by the same species of Chalcidinae. Nevertheless, studies designed to measure the effectiveness of the relationship with ants, have shown that percentages of parasitism decrease significantly in the presence of ants (Atsatt 1981a, Pierce & Mead 1981, Pierce & Nash 1999, and that not all the species of ants are equally effective in the defense of larvae (Fraser et al 2001, Kaminski & Rodrigues 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In these subalpine meadows, previous research has already demonstrated how a shift in phenology can disrupt several important mutualisms (Saavedra et al 2003, Diez et al 2012, McKinney et al 2012). Due to the important role ants play in this specific system as well as most terrestrial ecosystems as mutualists, predators, and nutrient distribution (Hö lldobler and Wilson 1990), shifts in individual species' distributions can play an important role (Fraser et al 2001). A changing climate selects for success of different genotypes within a given species (Rank andDahlhoff 2002, Skelly et al 2007).…”
Section: Discussionmentioning
confidence: 99%